Challenges in Arabic Language Instruction: Evaluating the Al-Syam’iyyah Al-Syafawiyyah Method as an Alternative Teaching Approach - Jailani, Mohammad; Khusni Akbar, Tian Khusni; Perawironegoro, Djamaluddin; Huda, Miftachul (UIN Sunan Gunung Djati Bandung, 2023)
The prevailing issues in education have shown that schools and teachers have struggled to implement effective Arabic learning methodologies. While teachers comprehend various teaching approaches, these methods are often ineffective for students. This study aimed to analyze the effectiveness of the al-sam'iyyah al-syafawiyyah learning method in teaching Arabic at SMK Muhammadiyah 3 Yogyakarta. The research used a qualitative method to involve teachers and students within SMK Muhammadiyah 3 Yogyakarta. Data collection methods included interviews, observations, and documentation. The analysis followed Miles and Huberman's data display, reduction, and verification techniques. Triangulation was utilized to fortify the research data from fieldwork and primary sources (literature). The study revealed significant disparities between the al-sam'iyyah al-syafawiyyah method and the conventional teaching approaches practiced by teachers at the school. According to teacher feedback, the predominant method used thus far has been lecturing, resulting in 60% of students not mastering the 'mufradÄt.' Conversely, the implications of the al-sam'iyyah al-syafawiyyah method indicated highly engaged, active, and practical students. This method primarily focuses on enhancing student concentration through listening, imitating teacher explanations, and practicing the fluency of 'mufradÄt.'